The Optimal Use of Natural Resources in Light of Intergenerational Equity - Alicja M. GRACZYK (Communications of International Proceedings, 2025)
This paper provides an overview of those economic models of resource management which bear associations with the realization of the principle of intergenerational equity as the key element in effective implementation of the sustainable development postulates. Sustainable development entails the preservation of capital for future generations – most particularly: the natural capital. The paper represents an attempt at identifying those of the presently adopted economic models of resource management which are best suited to reinforce the realization of the idea of intergenerational equity and the durable qualities of sustainable development. The following methods were employed in the study: identification, critical analysis, comparative analysis, and expert evaluation of economic models. Based on definitions of fundamental concepts established in the initial section of the paper, the author identified those of the presently adopted models which ensure the realization of the postulate of intergenerational equity. Three main models were identified: the utilitarian criterion, the Rawls criterion, and the Chichilnisky criterion. These were analysed and evaluated for their utility, validity, and conformity with the principle of intergenerational equity. The findings of the study are in favour of the Chichilnisky criterion as best suited for the realization of the idea of equity, both inter- and intra-generational, as it takes into account the interests of both the present and the future generations. This criterion was also found to best represent the durability aspects of sustainable development.
Keywords: sustainable development; generational equity; natural resources